Feminist Collections, v.23, no.2 (winter 2002) - (:unkn) unknown (My University, 2002)
Subtitle: A Quarterly of Women's Studies Resources. 48p.
FROM THE EDITORS. BOOK REVIEWS: The Domestic Is Global: Household Workers Around the World, by Carol Mitchell. Domestic Violence Texts: A Review of Teaching Resources, by Karen E. Muench. FEMINIST VISIONS: Playing Against Stereotypes: Videos on Women in Popular Music, by Shannon L. Green. Feminism, Women Workers, and Globalization: Films and Books, by Jean Grossholtz. COMPUTER TALK: Compiled by JoAnne Lehman. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard and others. PERIODICAL NOTES: Compiled by JoAnne Lehman. ITEMS OF NOTE: Compiled by Teresa Fernandez. BOOKS/AV RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Household Workers; Domestic Violence; Video Reviews; Globalization